Evaluation of the surface energy of dispersed aluminium oxide using owens-wendt theory - Myronyuk, Oleksiy; Baklan, Denys; Nudchenko, Lyudmyla (Technology audit and production reserves, 2020)
Knowing the value of the surface energy of powder materials allows to predict the interaction of the solid phase with liquids, the formation of stable dispersions, durable and resistant to aggressive factors of composites. The application of the Owens-Wendt model for determining the change in the surface energy of aluminium oxide modified by various water repellents is considered. Also, to determine the contact angle of the surface of the modified material, the Washburn method is used, which consists in determining the rate of capillary rise of the test fluid. This method is chosen due to low requirements in the accuracy of measuring equipment and at the same time shows a high degree of accuracy of the results. The object of research is a method for determining the surface energy of powder materials, using aluminium oxide modified with polymethylhydrosiloxane as an example. Surface modifications of the aluminium oxide powder are carried out in a xylene suspension. In the work, the determination of surface energy is carried out in accordance with the Owens-Wendt theory by the graphical method in accordance with the obtained values of the contact angle of the material according to the Washburn method. It is established the shape of the particles of aluminium oxide and their average size, and also calculated the specific surface of the material. A modifier, polymethylhydrosiloxane, is found, with the help of which it is possible to obtain a stable superhydrophobic state, and the optimal concentration by determining the contact angles of the powder material with test liquids according to the method proposed by Washburn. To increase the accuracy of determining the surface energy of the material according to the Washburn method, a mixture of water with ethanol is used, and the components of surface tension are calculated. It is shown that the values of the contact angle of the surface of the dispersed material obtained using a mixture as a test liquid can be used to calculate the values of the components of the surface energy of aluminium oxide. In this case, there is a lack of error in the form of the Cassie state, which is observed for hydrophobic dispersed materials when using water as a test fluid.